PENGARUH PEMBERIAN JUS NANAS DAN PLUM TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM - Retno Arum Sari (2022)
Perineal wound healing requires adequate nutrition as a way to treat wounds to avoid infection. There are several ways that can be done to accelerate the healing of perineal sutures, one of which is by consuming vitamins. Wounds resulting from a torn birth canal can become a breeding ground for bacteria if not treated properly. Vitamins are believed to help the formation of collagen which is needed in forming new tissue so as to speed up wound healing. The purpose of this study was to determine the effect of giving pineapple and plum juice on perineal wound healing in post partum mothers. The design of this research is quasi-experimental with pretest-posttest with control group. The sampling technique used in this study was accidental sampling involving 66 post partum mothers. The data analysis used is the Mc nemar test with a P value of 0,000. The results of this study indicate that pineapple and plum juice have a significant effect on perineal wound healing in post partum mothers. In this study, it is hoped that mothers can apply pineapple and plum juice interventions by making their own to help heal perineal sutures.Keywords : Pineapple and plum juice, Perineal wound healing, Post partum